موقف وزارة ياسين الهاشمي الثانية (17 آذار 1935-29 تشرين الأول 1936) من مطالب الشيعة - العكام عبد الامير هاي (مجلة كلية التربية, 2018)
موقف وزارة ياسين الهاشمي الثانية (17 آذار 1935-29 تشرين الأول 1936) من مطالب الشيعة